2020
DOI: 10.1017/s1368980020005145
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, health and pro-breast-feeding policies and programmes associated with breast-feeding duration in Latin American countries

Abstract: Objective: To describe the duration of breast-feeding between 1990 and 2013 and to estimate the association between breast-feeding duration and sociodemographic, health and pro-breast-feeding policies and programmes in Latin American countries. Design: This is a cross-sectional study with data from Demographic and Health Surveys programme conducted in Bolivia, Brazil, Colombia, Peru and the Dominican Republic between 1990 and 2013. The median duration of breast-feeding was estimated by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Similar patterns were observed for public health center visits at birth, with 84% of women who breastfed for ≥4 months *Numbers summarized with (median, IQR) unless otherwise noted. 1 Summarized with rank sum. 2 Summarized with Fisher exact when a cell was ≤5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar patterns were observed for public health center visits at birth, with 84% of women who breastfed for ≥4 months *Numbers summarized with (median, IQR) unless otherwise noted. 1 Summarized with rank sum. 2 Summarized with Fisher exact when a cell was ≤5.…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of factors associated with the continuation of breastfeeding for at least 4 months, Cesarean mode of birth [unadjusted RR = 0.77, 95% CI: (0.64-0.92), P = .01], unknown mode of birth [RR = 0.27, 95% CI: (0.07-1.02), P = .05], visiting a public antenatal site during pregnancy [unadjusted RR = 2.63, 95% CI: (1.22-5.20), P < .01], health center visited at birth [unadjusted RR = 1.49, 95% CI: (1.18-1.88), P < .01], time between most recent and previous pregnancy [unadjusted RR = 1.01, 95% CI: (0.99-1.03), P = .08], employment status [unadjusted RR = 0.87, 95% CI: (0.75-1.01), P = .07] and having a secondary [unadjusted RR = 0.89, 95% CI: (0.77-1.01), P = .07] and *Numbers summarized with (median, IQR) unless otherwise noted. 1 Summarized with rank sum. 2 Summarized with Fisher exact when a cell was ≤5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Victora et al (55) observed that in 98 low-and middle-income countries, mothers with lower economic income were more likely to breastfeed longer than mothers with higher income. Following the same rationale, Lamounier et al (56) associated the shorter duration of breast-feeding with higher levels of maternal education and higher income quintiles in five Latin American countries. However, despite the differences found between the per capita income brackets, it is noteworthy that our entire sample lived in extreme poverty, which can explain, at least in part, the differences observed.…”
Section: Discussionmentioning
confidence: 98%
“…However, the frequency of EBF decreases the older the age of the child (67.6% in children aged 0 months vs. 22.2% in children aged 5 months), reflecting a shorter duration of EBF in this region ( 17 ). Within the LAC countries, socioeconomic determinants influencing EBF practices have been observed, with a high educational and economic level of the mother being positively associated with the frequency and duration of EBF ( 18 , 19 ). In Peru, the Demographic and Family Health Survey (ENDES–acronym in Spanish) shows that EBF increased from 65.2% in 2015 to 68.4% in 2020 ( 20 ).…”
Section: Introductionmentioning
confidence: 99%